A method for manufacturing a special tensile drag cable

By adding tensile reinforcement material to the cable jacket, the problem of traditional cables being easily damaged under harsh conditions is solved, which significantly improves tensile and wear resistance, extends the cable life and improves safety.

CN119132754BActive Publication Date: 2025-04-18YANGZHOU HONGFEI CABLE LIGHTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411296569.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-04-18
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Traditional cables are prone to outer skin damage and internal wire breakage under high-strength drag, frequent bending and harsh climate conditions, resulting in cable failure and may cause safety accidents.

Method used

Using a special tensile-resistant drag cable manufacturing method, a tensile cable jacket is formed by mixing low-density polyethylene, ethylene-vinyl acetate copolymer, butyl rubber, tensile reinforcement, calcium stearate, phthalate, anti-aging agent TMQ and accelerator M evenly, and then forming a tensile cable jacket through an extruder. Tensile reinforcement consists of polysulfone, carbon fiber and modifiers, which improve the tensile and wear resistance of the cable through complex chemical reactions and physical modification treatments.

Benefits of technology

It significantly improves the tensile and wear resistance of the cable, can withstand high-strength drag and frequent bending, and operates stably for a long time in harsh climates, extending the service life of the cable, improving safety and reducing maintenance costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of special cables, and in particular to a method for manufacturing a special tensile dragging cable, which is used to solve the problem that the existing cables are prone to outer sheath damage and internal conductor breakage when facing high-intensity dragging, frequent bending and severe weather conditions, resulting in cable failure and even safety accidents. The manufacturing method can effectively improve the tensile performance and wear resistance of the special tensile dragging cable by adding tensile reinforcement material to the tensile cable jacket, can withstand high-intensity dragging and frequent bending, can operate stably for a long time under severe weather conditions, significantly improves the service life and safety of the cable, and reduces maintenance costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of special cables, and in particular to a method for manufacturing a special tensile-resistant drag cable. Background Art

[0002] In modern society, with the rapid development of science and technology and the continuous growth of energy demand, cables, as an important carrier of power and signal transmission, are also constantly evolving. With the continuous development of modern industry, the performance requirements for cables are getting higher and higher. Especially in some special environments, such as marine engineering, mining, large-scale machinery and equipment, cables need to have excellent tensile and dragging properties to ensure their reliable operation under harsh conditions. However, traditional cable jacket materials often have insufficient mechanical properties and poor wear resistance, which makes it difficult to meet the needs of complex working environments. Especially when facing high-intensity dragging, frequent bending and harsh weather conditions, the outer skin is often damaged and the internal wires are broken, resulting in cable failure and even safety accidents. Therefore, it is of great significance to develop a manufacturing method for special tensile and dragging cables. Summary of the invention

[0003] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a method for manufacturing a special tensile-resistant drag cable, which solves the problem that the existing cables are prone to outer skin damage and internal wire breakage when facing high-intensity dragging, frequent bending and severe weather conditions, resulting in cable failure and even safety accidents.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for manufacturing a special tension-resistant drag cable comprises the following steps:

[0006] Step 1: Weigh 70-80 parts of low-density polyethylene, 25-35 parts of ethylene-vinyl acetate copolymer, 20-26 parts of butadiene rubber, 3-13 parts of tensile reinforcement material, 2-4 parts of calcium stearate, 1-3 parts of phthalate, 0.5-1.5 parts of antioxidant TMQ and 0.3-0.5 parts of accelerator M according to weight parts, and set aside;

[0007] Step 2: Add low-density polyethylene, ethylene-vinyl acetate copolymer, butadiene rubber, tensile reinforcement material, calcium stearate, phthalate, antioxidant TMQ and accelerator M into a mixer and mix evenly, then add them into an extruder and melt-extrude them onto the outside of the copper wire core to form a tensile cable jacket to obtain a special tensile drag cable.

[0008] As a further solution of the present invention: the tensile reinforcement material is prepared by the following steps:

[0009] Step A1: Add polysulfone and dichloromethane to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 1-1.5 hours at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, then add chloromethyl octyl ether and tin tetrachloride and continue to stir and react for 15-20 minutes, then heat to 35-40° C. and continue to stir and react for 2-3 hours. After the reaction is completed, cool the reaction product to room temperature, then add it to anhydrous ethanol and let it stand for precipitation, then vacuum filter, place the filter cake in a vacuum drying oven, and dry it at a temperature of 60-65° C. for 8-10 hours to obtain intermediate 1;

[0010] Step A2: 2,2-bis(3-nitrophenyl)hexafluoropropane, 10% palladium carbon and anhydrous ethanol are added to a four-necked flask equipped with a stirrer, a thermometer, an air guide tube, a constant pressure dropping funnel and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction for 20-30 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min. Then, a hydrazine hydrate solution is added dropwise while stirring, and the dropping rate is controlled to be 1-2 drops / s. After the dropwise addition is completed, the mixture is heated to reflux and the stirring reaction is continued for 4-6 hours. After the reaction is completed, the reaction product is filtered while hot, and the filtrate is added to ice water to precipitate, and then vacuum filtered. The filter cake is washed with distilled water for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 60-65° C. for 4-5 hours to obtain intermediate 2;

[0011] Step A3: Add intermediate 1, intermediate 2, anhydrous potassium carbonate and N-methylpyrrolidone to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir the reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 15-20 min, then raise the temperature to 130-135° C. and continue stirring the reaction for 8-10 h. After the reaction is completed, cool the reaction product to room temperature, then add it to ethyl acetate to precipitate, then vacuum filter, wash the filter cake with distilled water 3-5 times, then place it in a vacuum drying oven, and dry it at a temperature of 60-65° C. for 8-10 h to obtain intermediate 3;

[0012] Step A4: Add intermediate 3, (3-chloropropyl)triethoxysilane, anhydrous potassium carbonate, potassium iodide and N-methylpyrrolidone to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, introduce nitrogen protection, stir the reaction at a temperature of -5-0°C and a stirring rate of 300-400r / min for 10-15min, then heat to 80-85°C and continue stirring the reaction for 8-12h. After the reaction is completed, cool the reaction product to room temperature, vacuum filter, and rotary evaporate the filtrate to remove the solvent, then wash with anhydrous ethanol 3-5 times, and then place it in a vacuum drying oven and dry it at a temperature of 60-65°C for 8-10h to obtain modified polysulfone;

[0013] Step A5: Add modified polysulfone, N, N-dimethylacetamide and anhydrous acetone to a three-necked flask equipped with an agitator, a thermometer and a nitrogen inlet tube, introduce nitrogen protection, stir and react for 1-2 hours at a temperature of 45-50°C and a stirring rate of 300-400r / min, then add coated carbon fiber and deionized water and continue to stir and react for 3-4 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at a temperature of 80-85°C for 3-5 hours to obtain a tensile reinforcement material.

[0014] As a further solution of the present invention: the usage ratio of the polysulfone, dichloromethane, chloromethyl octyl ether and tin tetrachloride in step A1 is 10g:120-130mL:30-35mL:4.5-5.5g; the model of the polysulfone is Udel PSU P-3500LCD.

[0015] As a further scheme of the present invention: the usage ratio of the 2,2-bis(3-nitrophenyl)hexafluoropropane, 10% palladium on carbon, anhydrous ethanol and hydrazine hydrate solution in step A2 is 10mmol:4.2-5.6g:100-120mL:30-40g; the mass fraction of the hydrazine hydrate solution is 80%.

[0016] As a further scheme of the present invention: the usage ratio of the intermediate 1, intermediate 2, anhydrous potassium carbonate and N-methylpyrrolidone in step A3 is 1 g: 25-30 mL: 30-35 mmol: 25-30 mmol.

[0017] As a further scheme of the present invention: the usage ratio of the intermediate 3, (3-chloropropyl)triethoxysilane, anhydrous potassium carbonate, potassium iodide and anhydrous toluene in step A4 is 1g:25-30mmol:30-35mmol:1-2mmol:50-60mL

[0018] As a further solution of the present invention: the usage ratio of the modified polysulfone, N,N-dimethylacetamide, anhydrous acetone, coated carbon fiber and deionized water in step A5 is 2.5-7.5g:85-90mL:10-12mL:5g:10-15mL.

[0019] As a further solution of the present invention: the coated carbon fiber is prepared by the following steps:

[0020] Step B1: Add carbon fiber and anhydrous acetone to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to reflux and continue stirring and reacting for 20-30 hours. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, wash the filter cake with anhydrous ethanol and distilled water for 3-5 times in turn, then place it in a vacuum drying oven, and dry it at a temperature of 60-65°C for 4-5 hours to obtain clean carbon fiber;

[0021] Step B2: Add tetraethyl orthosilicate, deionized water and anhydrous ethanol to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then adjust the pH to 1-2 with a hydrochloric acid solution, then add polyvinyl pyrrolidone, clean the carbon fiber and continue to stir and react for 15-20 minutes at a temperature of 45-50°C, then adjust the pH to 5-6 with an ammonia solution, and then continue to stir and react for 20-30 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, the filter cake is washed with distilled water 3-5 times, and then placed in a vacuum drying oven, and dried at a temperature of 60-65°C for 10-15 hours to obtain a coated carbon fiber.

[0022] As a further solution of the present invention: the usage ratio of the carbon fiber and anhydrous acetone in step B1 is 2g:25-30mL; the carbon fiber is T700SC-12K carbon fiber.

[0023] As a further scheme of the present invention: the dosage ratio of the tetraethyl orthosilicate, deionized water, anhydrous ethanol, polyvinyl pyrrolidone and clean carbon fiber in step B2 is 20-25mL: 15-25mL: 80-90mL: 0.5-1.5g: 2g; the mass fraction of the hydrochloric acid solution is 20-25%, and the molar concentration of the ammonia solution is 1mol / L.

[0024] Beneficial effects of the present invention:

[0025] The invention discloses a method for manufacturing a special tensile dragging cable. The method comprises the following steps: adding low-density polyethylene, ethylene-vinyl acetate copolymer, butadiene rubber, tensile reinforcement material, calcium stearate, phthalate, antioxidant TMQ and accelerator M into a mixer and mixing them evenly; then adding the mixture into an extruder and molten-extruded them onto the outside of a copper wire core to form a tensile cable jacket, thereby obtaining the special tensile dragging cable. The manufacturing method can effectively improve the tensile performance and wear resistance of the special tensile dragging cable by adding the tensile reinforcement material into the tensile cable jacket, the cable can withstand high-intensity dragging and frequent bending, can stably operate for a long time under adverse climatic conditions, significantly improves the service life and safety of the cable, and reduces maintenance costs.

[0026] In the process of preparing special tensile drag cables, a tensile reinforcement material is first prepared, and impurities on the surface of carbon fiber are cleaned by anhydrous acetone to obtain clean carbon fiber. Then, tetraethyl orthosilicate is used as a raw material, and nano-silicon dioxide is loaded on the surface of the clean carbon fiber by a sol-gel method to obtain a coated carbon fiber. Then, polysulfone and chloromethyl octyl ether are reacted to introduce chloromethyl groups on the benzene ring in the molecular structure of polysulfone to obtain intermediate 1. Then, 2,2-bis(3-nitrophenyl)hexafluoropropane and hydrazine hydrate are reacted to hydrate the nitrate on 2,2-bis(3-nitrophenyl)hexafluoropropane. The group is reduced to an amino group to obtain intermediate 2, and then intermediate 1 and intermediate 2 react, the chlorine atom on intermediate 1 reacts with an amino group on intermediate 2, and amino and trifluoromethyl are introduced at the same time to obtain intermediate 3, and then intermediate 3 and (3-chloropropyl) triethoxysilane react, the amino group on intermediate 3 reacts with the chlorine atom on (3-chloropropyl) triethoxysilane, and a large number of siloxane groups are introduced to obtain modified polysulfone, and finally the coated carbon fiber is modified by using the modified polysulfone, and the siloxane on the modified polysulfone is hydrolyzed to form silanol connected to the particle surface of the coated carbon fiber to form The polysulfone protective layer is used to wrap the coated carbon fiber to obtain a tensile reinforcement material; carbon fiber has the advantages of high tensile strength, light weight, high rigidity and good heat resistance. After being added to the tensile cable jacket, when external force acts on the cable, the carbon fiber can effectively disperse and bear most of the stress, thereby significantly improving the tensile strength of the cable. Loading nano-silicon dioxide on the carbon fiber can not only significantly increase the roughness of the carbon fiber surface, increase the wettability and adsorption capacity between the carbon fiber and the matrix, and enhance the bonding force, but also greatly improve the hardness and wear resistance of the carbon fiber, while making the activity of the carbon fiber surface The increase in the number of functional groups makes it easier for the coated carbon fiber to be grafted with modified polysulfone, and the interface compatibility between the coated carbon fiber and the tensile cable jacket is greatly improved after grafting modified polysulfone. At the same time, a large number of benzene rings, sulfone groups and trifluoromethyl groups are introduced to reduce the brittleness of the carbon fiber and greatly improve the mechanical properties and environmental stability of the carbon fiber, thereby enhancing the overall toughness and impact resistance of the tensile cable jacket, so that the cable can better resist impact, vibration and dragging and will not be easily damaged. The presence of trifluoromethyl groups improves its lubricity and wear resistance, thereby enhancing the overall performance of the cable. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1:

[0029] This embodiment is a method for manufacturing a special tensile drag cable, comprising the following steps:

[0030] Step S1: 2 g of T700SC-12K carbon fiber and 25 mL of anhydrous acetone were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred for reaction at a temperature of 25 ° C and a stirring rate of 300 r / min for 20 min, and then the mixture was heated to reflux and continued to stir for 20 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with anhydrous ethanol and distilled water for 3 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 60 ° C for 4 h to obtain clean carbon fiber;

[0031] Step S2: 20 mL of tetraethyl orthosilicate, 15 mL of deionized water and 80 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for 20 min at a temperature of 25 ° C and a stirring rate of 300 r / min, and then the pH was adjusted to 2 with a 20% hydrochloric acid solution by mass, and then 0.5 g of polyvinyl pyrrolidone and 2 g of clean carbon fiber were added and the temperature was raised to 45 ° C and the stirring reaction was continued for 15 min, and then the pH was adjusted to 5 with a molar concentration of 1 mol / L ammonia solution, and then the stirring reaction was continued for 20 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, the filter cake was washed with distilled water 3 times, and then placed in a vacuum drying oven, and dried at a temperature of 60 ° C for 10 h to obtain a coated carbon fiber;

[0032] Step S3: 10 g of Udel PSU P-3500LCD polysulfone and 120 mL of dichloromethane were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at 25° C. and a stirring rate of 300 r / min for 1 h, and then 30 mL of chloromethyl octyl ether and 4.5 g of tin tetrachloride were added and stirred for reaction for 15 min, and then the temperature was raised to 35° C. and stirred for reaction for 2 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to anhydrous ethanol and allowed to stand for precipitation, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at 60° C. for 8 h to obtain intermediate 1;

[0033] Step S4: 10mmol 2,2-bis(3-nitrophenyl)hexafluoropropane, 4.2g 10% palladium carbon and 100mL anhydrous ethanol were added to a four-necked flask equipped with a stirrer, a thermometer, an air guide tube, a constant pressure dropping funnel and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 25°C and a stirring rate of 300r / min for 20min, and then 30g of a hydrazine hydrate solution with a mass fraction of 80% was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the dropwise addition was completed, the mixture was heated to reflux and continued to stir and react for 4h. After the reaction was completed, the reaction product was filtered while hot, and the filtrate was added to ice water to precipitate, and then vacuum filtered. The filter cake was washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 60°C for 4h to obtain intermediate 2;

[0034] Step S5: 1 g of intermediate 1, 25 mL of intermediate 2, 30 mmol of anhydrous potassium carbonate and 25 mmol of N-methylpyrrolidone were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at 25° C. and a stirring rate of 300 r / min for 15 min, and then the temperature was raised to 130° C. and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ethyl acetate to precipitate, and then vacuum filtered. The filter cake was washed with distilled water 3 times, and then placed in a vacuum drying oven and dried at 60° C. for 8 h to obtain intermediate 3;

[0035] Step S6: 1 g of intermediate 3, 25 mmol (3-chloropropyl) triethoxysilane, 30 mmol anhydrous potassium carbonate, 1 mmol potassium iodide and 50 mL N-methylpyrrolidone were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen protection was introduced. The reaction was stirred for 10 min at a temperature of -5 ° C and a stirring rate of 300 r / min, and then the temperature was raised to 80 ° C and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, the filtrate was rotary evaporated to remove the solvent, and then washed with anhydrous ethanol 3 times, and then placed in a vacuum drying oven, and dried at a temperature of 60 ° C for 8 h to obtain modified polysulfone;

[0036] Step S7: 2.5 g of modified polysulfone, 85 mL of N, N-dimethylacetamide and 10 mL of anhydrous acetone were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen protection was introduced. The mixture was stirred at a temperature of 45° C. and a stirring rate of 300 r / min for 1 h, and then 5 g of coated carbon fiber and 10 mL of deionized water were added to continue stirring the reaction for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 80° C. for 3 h to obtain a tensile reinforcement material;

[0037] Step S8: 70 parts of low-density polyethylene, 25 parts of ethylene-vinyl acetate copolymer, 20 parts of butadiene rubber, 3 parts of tensile reinforcement material, 2 parts of calcium stearate, 1 part of phthalate, 0.5 parts of antioxidant TMQ and 0.3 parts of accelerator M were weighed in parts by weight for later use;

[0038] Step S9: Add low-density polyethylene, ethylene-vinyl acetate copolymer, butadiene rubber, tensile reinforcement material, calcium stearate, phthalate, antioxidant TMQ and accelerator M into a mixer and mix evenly, then add them into an extruder and melt-extrude them onto the outside of the copper wire core to form a tensile cable jacket to obtain a special tensile drag cable.

[0039] Embodiment 2:

[0040] This embodiment is a method for manufacturing a special tensile drag cable, comprising the following steps:

[0041] Step S1: 2 g of T700SC-12K carbon fiber and 28 mL of anhydrous acetone were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred for reaction at a temperature of 28 ° C and a stirring rate of 350 r / min for 25 min, and then the mixture was heated to reflux and continued to stir for 25 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with anhydrous ethanol and distilled water for 4 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 62 ° C for 4.5 h to obtain clean carbon fiber;

[0042] Step S2: 22 mL of tetraethyl orthosilicate, 20 mL of deionized water and 85 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred for 25 min at a temperature of 28 ° C and a stirring rate of 350 r / min, and then the pH was adjusted to 1.5 with a 22% hydrochloric acid solution by mass, and then 1 g of polyvinyl pyrrolidone and 2 g of clean carbon fiber were added and the mixture was heated to 48 ° C and continued to stir for 18 min, and then the pH was adjusted to 5.5 with a molar concentration of 1 mol / L ammonia solution, and then the mixture was stirred for 25 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filter cake was washed with distilled water 4 times, and then placed in a vacuum drying oven and dried at a temperature of 62 ° C for 12 h to obtain a coated carbon fiber;

[0043] Step S3: 10 g of Udel PSU P-3500LCD polysulfone and 125 mL of dichloromethane were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at 28° C. and 350 r / min for 1 h, and then 32 mL of chloromethyl octyl ether and 5 g of tin tetrachloride were added for 18 min, and then the mixture was heated to 38° C. and stirred for 2.5 h. After the reaction, the reaction product was cooled to room temperature, and then added to anhydrous ethanol and allowed to stand for precipitation, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at 62° C. for 9 h to obtain intermediate 1;

[0044] Step S4: 10 mmol 2,2-bis(3-nitrophenyl)hexafluoropropane, 4.9 g 10% palladium carbon and 110 mL anhydrous ethanol were added to a four-necked flask equipped with a stirrer, a thermometer, an air guide tube, a constant pressure dropping funnel and a reflux condenser, and nitrogen was introduced for protection. The reaction was stirred for 25 min at a temperature of 28 ° C and a stirring rate of 350 r / min. Then, 35 g of a hydrazine hydrate solution with a mass fraction of 80% was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the dropwise addition was completed, the temperature was raised to reflux and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was filtered while hot, and the filtrate was added to ice water to precipitate, and then vacuum filtered. The filter cake was washed 4 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 62 ° C for 4.5 h to obtain intermediate 2;

[0045] Step S5: 1 g of intermediate 1, 28 mL of intermediate 2, 32 mmol of anhydrous potassium carbonate and 28 mmol of N-methylpyrrolidone were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at 28° C. and a stirring rate of 350 r / min for 18 min, and then the temperature was raised to 132° C. and the stirring reaction was continued for 9 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ethyl acetate to precipitate, and then vacuum filtered. The filter cake was washed with distilled water 4 times, and then placed in a vacuum drying oven and dried at 62° C. for 9 h to obtain intermediate 3;

[0046] Step S6: 1 g of intermediate 3, 28 mmol (3-chloropropyl) triethoxysilane, 32 mmol anhydrous potassium carbonate, 1.5 mmol potassium iodide and 55 mL N-methylpyrrolidone were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen protection was introduced. The reaction was stirred for 12 min at a temperature of -3 ° C and a stirring rate of 350 r / min, and then the temperature was raised to 82 ° C and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, the filtrate was rotary evaporated to remove the solvent, and then washed with anhydrous ethanol 4 times, and then placed in a vacuum drying oven, and dried at a temperature of 62 ° C for 9 h to obtain modified polysulfone;

[0047] Step S7: 5 g of modified polysulfone, 88 mL of N, N-dimethylacetamide and 11 mL of anhydrous acetone were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen protection was introduced. The mixture was stirred for reaction at a temperature of 48 ° C and a stirring rate of 350 r / min for 1.5 h, and then 5 g of coated carbon fiber and 12 mL of deionized water were added to continue stirring for 3.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 82 ° C for 4 h to obtain a tensile reinforcement material;

[0048] Step S8: weigh 75 parts of low-density polyethylene, 30 parts of ethylene-vinyl acetate copolymer, 23 parts of butadiene rubber, 8 parts of tensile reinforcement material, 3 parts of calcium stearate, 2 parts of phthalate, 1 part of antioxidant TMQ and 0.4 part of accelerator M according to weight parts, and set aside;

[0049] Step S9: Add low-density polyethylene, ethylene-vinyl acetate copolymer, butadiene rubber, tensile reinforcement material, calcium stearate, phthalate, antioxidant TMQ and accelerator M into a mixer and mix evenly, then add them into an extruder and melt-extrude them onto the outside of the copper wire core to form a tensile cable jacket to obtain a special tensile drag cable.

[0050] Embodiment 3:

[0051] This embodiment is a method for manufacturing a special tensile drag cable, comprising the following steps:

[0052] Step S1: 2 g of T700SC-12K carbon fiber and 30 mL of anhydrous acetone were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred for reaction at a temperature of 30 ° C and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to reflux and continued to stir for 30 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with anhydrous ethanol and distilled water for 5 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 65 ° C for 5 h to obtain clean carbon fiber;

[0053] Step S2: 25 mL of tetraethyl orthosilicate, 25 mL of deionized water and 90 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred for reaction at a temperature of 30°C and a stirring rate of 400 r / min for 30 min, and then the pH was adjusted to 1 with a 25% hydrochloric acid solution by mass, and then 1.5 g of polyvinyl pyrrolidone and 2 g of clean carbon fiber were added and the mixture was heated to 50°C and stirred for reaction for 20 min, and then the pH was adjusted to 6 with a 1 mol / L ammonia solution, and then the mixture was stirred for reaction for 30 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered, and the filter cake was washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at 65°C for 15 h to obtain a coated carbon fiber;

[0054] Step S3: 10 g of Udel PSU P-3500LCD polysulfone and 130 mL of dichloromethane were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at 30° C. and 400 r / min for 1.5 h. Then, 35 mL of chloromethyl octyl ether and 5.5 g of tin tetrachloride were added, and the mixture was stirred for 20 min. Then, the mixture was heated to 40° C. and stirred for 3 h. After the reaction, the reaction product was cooled to room temperature, and then added to anhydrous ethanol and allowed to stand for precipitation. Then, the filter cake was vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at 65° C. for 10 h to obtain an intermediate 1.

[0055] Step S4: 10 mmol 2,2-bis(3-nitrophenyl)hexafluoropropane, 5.6 g 10% palladium carbon and 120 mL anhydrous ethanol were added to a four-necked flask equipped with a stirrer, a thermometer, an air guide tube, a constant pressure dropping funnel and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then 40 g of a hydrazine hydrate solution with a mass fraction of 80% was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the dropwise addition was completed, the temperature was raised to reflux and the stirring reaction was continued for 6 h. After the reaction was completed, the reaction product was filtered while hot, and the filtrate was added to ice water to precipitate, and then vacuum filtered. The filter cake was washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 5 h to obtain intermediate 2;

[0056] Step S5: 1 g of intermediate 1, 30 mL of intermediate 2, 35 mmol of anhydrous potassium carbonate and 30 mmol of N-methylpyrrolidone were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred at 30° C. and a stirring rate of 400 r / min for 20 min, and then the temperature was raised to 135° C. and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ethyl acetate to precipitate, and then vacuum filtered. The filter cake was washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at 65° C. for 10 h to obtain intermediate 3;

[0057] Step S6: 1 g of intermediate 3, 30 mmol (3-chloropropyl) triethoxysilane, 35 mmol anhydrous potassium carbonate, 2 mmol potassium iodide and 60 mL N-methylpyrrolidone were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen protection was introduced. The reaction was stirred for 15 min at a temperature of 0°C and a stirring rate of 400 r / min, and then the temperature was raised to 85°C and the stirring reaction was continued for 12 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, the filtrate was rotary evaporated to remove the solvent, and then washed with anhydrous ethanol 5 times, and then placed in a vacuum drying oven, and dried at a temperature of 65°C for 10 h to obtain modified polysulfone;

[0058] Step S7: 7.5 g of modified polysulfone, 90 mL of N, N-dimethylacetamide and 12 mL of anhydrous acetone were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen protection was introduced. The mixture was stirred at a temperature of 50° C. and a stirring rate of 400 r / min for 2 h, and then 5 g of coated carbon fiber and 15 mL of deionized water were added to continue stirring the reaction for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 85° C. for 5 h to obtain a tensile reinforcement material;

[0059] Step S8: 80 parts of low-density polyethylene, 35 parts of ethylene-vinyl acetate copolymer, 26 parts of butadiene rubber, 13 parts of tensile reinforcement material, 4 parts of calcium stearate, 3 parts of phthalate, 1.5 parts of antioxidant TMQ and 0.5 parts of accelerator M were weighed according to weight parts and set aside;

[0060] Step S9: Add low-density polyethylene, ethylene-vinyl acetate copolymer, butadiene rubber, tensile reinforcement material, calcium stearate, phthalate, antioxidant TMQ and accelerator M into a mixer and mix evenly, then add them into an extruder and melt-extrude them onto the outside of the copper wire core to form a tensile cable jacket to obtain a special tensile drag cable.

[0061] Comparative Example 1:

[0062] This comparative example is a method for manufacturing a special tensile drag cable, comprising the following steps:

[0063] Step S1: 80 parts of low-density polyethylene, 35 parts of ethylene-vinyl acetate copolymer, 26 parts of butadiene rubber, 4 parts of calcium stearate, 3 parts of phthalate, 1.5 parts of antioxidant TMQ and 0.5 parts of accelerator M were weighed according to weight and set aside;

[0064] Step S2: Add low-density polyethylene, ethylene-vinyl acetate copolymer, butadiene rubber, calcium stearate, phthalate, antioxidant TMQ and accelerator M into a mixer and mix evenly, then add them into an extruder and melt-extrude them onto the outside of the copper wire core to form a tensile cable jacket, thereby obtaining a special tensile drag cable.

[0065] Comparative Example 2:

[0066] This comparative example is a method for manufacturing a special tensile drag cable, comprising the following steps:

[0067] Step S1: 80 parts of low-density polyethylene, 35 parts of ethylene-vinyl acetate copolymer, 26 parts of butadiene rubber, 13 parts of T700SC-12K carbon fiber, 4 parts of calcium stearate, 3 parts of phthalate, 1.5 parts of antioxidant TMQ and 0.5 parts of accelerator M were weighed according to weight parts and set aside;

[0068] Step S2: low-density polyethylene, ethylene-vinyl acetate copolymer, butadiene rubber, T700SC-12K carbon fiber, calcium stearate, phthalate, antioxidant TMQ and accelerator M are added to a mixer and mixed evenly, and then added to an extruder and melt-extruded to the outside of the copper wire core to form a tensile cable jacket to obtain a special tensile drag cable.

[0069] Comparative Example 3:

[0070] This comparative example is a method for manufacturing a special tensile drag cable, comprising the following steps:

[0071] Step S1: 80 parts of low-density polyethylene, 35 parts of ethylene-vinyl acetate copolymer, 26 parts of butadiene rubber, 13 parts of coated carbon fiber, 4 parts of calcium stearate, 3 parts of phthalate, 1.5 parts of antioxidant TMQ and 0.5 parts of accelerator M were weighed according to weight parts and set aside;

[0072] Step S2: low-density polyethylene, ethylene-vinyl acetate copolymer, butadiene rubber, coated carbon fiber, calcium stearate, phthalate, antioxidant TMQ and accelerator M are added to a mixer and mixed evenly, and then added to an extruder and melt-extruded to the outside of the copper wire core to form a tensile cable jacket to obtain a special tensile drag cable.

[0073] Comparative Example 4:

[0074] This comparative example is a method for manufacturing a special tensile drag cable, comprising the following steps:

[0075] Step S1: 80 parts of low-density polyethylene, 35 parts of ethylene-vinyl acetate copolymer, 26 parts of butadiene rubber, 13 parts of modified polysulfone, 4 parts of calcium stearate, 3 parts of phthalate, 1.5 parts of antioxidant TMQ and 0.5 parts of accelerator M were weighed in parts by weight for later use;

[0076] Step S2: low-density polyethylene, ethylene-vinyl acetate copolymer, butadiene rubber, modified polysulfone, calcium stearate, phthalate, antioxidant TMQ and accelerator M are added to a mixer and mixed evenly, and then added to an extruder and melt-extruded to the outside of the copper wire core to form a tensile cable jacket to obtain a special tensile drag cable.

[0077] The tensile cable jackets of the special tensile drag cables in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests, and the test results are shown in the following table:

[0078] sample <![CDATA[Tensile strength, MP a > Friction coefficient Example 1 55.08 0.069 Example 2 61.28 0.061 Example 3 67.69 0.053 Comparative Example 1 24.15 0.77 Comparative Example 2 47.56 0.29 Comparative Example 3 53.12 0.14 Comparative Example 4 39.93 0.093

[0079] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that the addition of tensile reinforcement material greatly improves the tensile strength of the tensile cable jacket and greatly reduces the friction coefficient, and finally the prepared cable has excellent tensile performance and wear resistance.

[0080] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0081] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for manufacturing a special tensile drag cable, characterized in that: The following steps are involved: Step 1: Weigh 70-80 parts of low-density polyethylene, 25-35 parts of ethylene-vinyl acetate copolymer, 20-26 parts of butadiene rubber, 3-13 parts of tensile reinforcement material, 2-4 parts of calcium stearate, 1-3 parts of phthalate, 0.5-1.5 parts of antioxidant TMQ and 0.3-0.5 parts of accelerator M according to weight parts, and set aside; Step 2: Add low-density polyethylene, ethylene-vinyl acetate copolymer, butadiene rubber, tensile reinforcement material, calcium stearate, phthalate, antioxidant TMQ and accelerator M into a mixer and mix them evenly, then add them into an extruder and melt extrude them onto the outside of the copper wire core to form a tensile cable jacket, thereby obtaining a special tensile drag cable; Wherein, the tensile reinforcement material is prepared by the following steps: Step A1: polysulfone and dichloromethane are stirred for reaction, and then chloromethyl octyl ether and tin tetrachloride are added and the stirring reaction is continued. After the reaction is completed, the reaction product is cooled, and then added to anhydrous ethanol and allowed to stand for precipitation, and then vacuum filtered, and the filter cake is dried to obtain intermediate 1; Step A2: 2,2-bis(3-nitrophenyl)hexafluoropropane, 10% palladium on carbon and anhydrous ethanol are stirred for reaction, and then a hydrazine hydrate solution is added dropwise while stirring. After the addition is completed, the stirring reaction is continued. After the reaction is completed, the reaction product is filtered while hot, and the filtrate is added into ice water to precipitate, and then vacuum filtered, and the filter cake is washed and dried to obtain intermediate 2; Step A3: stirring intermediate 1, intermediate 2, anhydrous potassium carbonate and N-methylpyrrolidone for reaction, cooling the reaction product after the reaction, then adding it into ethyl acetate to precipitate, then vacuum filtering, washing and drying the filter cake to obtain intermediate 3; Step A4: stirring the intermediate 3, (3-chloropropyl)triethoxysilane, anhydrous potassium carbonate, potassium iodide and N-methylpyrrolidone for reaction, cooling the reaction product after the reaction is completed, and then vacuum filtering, rotary evaporating the filtrate, and then washing and drying to obtain modified polysulfone; Step A5: Stir the modified polysulfone, N,N-dimethylacetamide and anhydrous acetone for reaction, then add the coated carbon fiber and deionized water and continue stirring the reaction. After the reaction is completed, cool the reaction product, then vacuum filter it, and dry the filter cake to obtain a tensile reinforcement material.

2. The method for manufacturing a special tensile drag cable according to claim 1, characterized in that: The usage ratio of the polysulfone, dichloromethane, chloromethyl octyl ether and tin tetrachloride in step A1 is 10g:120-130mL:30-35mL:4.5-5.5g.

3. The method for manufacturing a special tensile drag cable according to claim 1, characterized in that: The usage ratio of the 2,2-bis(3-nitrophenyl)hexafluoropropane, 10% palladium on carbon, anhydrous ethanol and hydrazine hydrate solution in step A2 is 10 mmol:4.2-5.6 g:100-120 mL:30-40 g; the mass fraction of the hydrazine hydrate solution is 80%.

4. The method for manufacturing a special tensile drag cable according to claim 1, characterized in that: The usage ratio of the intermediate 1, intermediate 2, anhydrous potassium carbonate and N-methylpyrrolidone in step A3 is 1 g: 25-30 mL: 30-35 mmol: 25-30 mmol.

5. The method for manufacturing a special tensile drag cable according to claim 1, characterized in that: The usage ratio of the intermediate 3, (3-chloropropyl)triethoxysilane, anhydrous potassium carbonate, potassium iodide and anhydrous toluene in step A4 is 1 g: 25-30 mmol: 30-35 mmol: 1-2 mmol: 50-60 mL.

6. The method for manufacturing a special tensile drag cable according to claim 1, characterized in that: The usage ratio of the modified polysulfone, N,N-dimethylacetamide, anhydrous acetone, coated carbon fiber and deionized water in step A5 is 2.5-7.5 g: 85-90 mL: 10-12 mL: 5 g: 10-15 mL.

7. The method for manufacturing a special tensile drag cable according to claim 1, characterized in that: The coated carbon fiber is prepared by the following steps: Step B1: stirring carbon fiber and anhydrous acetone to react, cooling the reaction product after the reaction is completed, and then vacuum filtering, washing and drying the filter cake to obtain clean carbon fiber; Step B2: Stir and react ethyl orthosilicate, deionized water and anhydrous ethanol, then adjust the pH with hydrochloric acid solution, then add polyvinyl pyrrolidone and clean carbon fiber and continue to stir and react, then adjust the pH with ammonia solution, then continue to stir and react, after the reaction is completed, cool the reaction product, then vacuum filter, wash and dry the filter cake to obtain coated carbon fiber.

8. The method for manufacturing a special tensile drag cable according to claim 7, characterized in that: The usage ratio of the carbon fiber and anhydrous acetone in step B1 is 2g:25-30mL.

9. The method for manufacturing a special tensile drag cable according to claim 7, characterized in that: The dosage ratio of the tetraethyl orthosilicate, deionized water, anhydrous ethanol, polyvinyl pyrrolidone and clean carbon fiber in step B2 is 20-25mL: 15-25mL: 80-90mL: 0.5-1.5g: 2g; the mass fraction of the hydrochloric acid solution is 20-25%, and the molar concentration of the ammonia solution is 1mol / L.

Citation Information

Patent Citations

  • Ploysulfone-nanofiber-toughened low-smoke, halogen-free and flame-retardant cable material for building and preparation method thereof

    CN104804283A

  • Polysulfone composite material as well as preparation method and application thereof

    CN114456600A